The Agreement to Buy and Sell Mu’athah in Supermarkets Reviewed from the Rules of Fiqhiyah Al-Istihsanu bil 'Urf - Yuliyanto Eko Prayitno; Febryan Hidayat; Prima Ariyo Widodo; Ahmad Ashari Ashshidiq; Alam Firman Syah (Demak Universal Journal of Islam and Sharia, 2024)
This study aims to investigate the law of mu’athah buying and selling transactions by referring to the rules of fiqhiyyah Al Istihsanu bil 'urf that occur in supermarkets. A qualitative approach with library research methods was used in this study, where data were obtained from books and journals. The data collection method used is descriptive analysis, with content analysis techniques. Research findings show that in business transactions, contracts have a vital role in people's lives, becoming the basis for various human activities. Akad becomes the framework of transactions in the Islamic economy, enabling the implementation of various business and economic activities. The Islamic view of the contract has no particular limitations, as long as it meets the requirements and pillars of the contract. However, with the progress of the times, the contract can be made directly, without using words, writing, or gestures, but rather through the actions of both parties that reflect the agreement, known as bai' mu’athah transactions. These transactions generally occur in supermarkets, using modern methods such as electronic media in the form of barcodes that can only be read by machines. Although this bai' mu’athah transaction does not fully meet the conditions and pillars of the contract, according to Maliki, the most basic is the custom that shows the agreement and willingness of both parties. Some Shafi'i scholars also allow bai' mu’athah transactions.